Analysis of altered microRNA expression profiles in peripheral blood mononuclear cells from patients with primary biliary cirrhosis. Issue 3 (26th February 2013) - Qin, Baodong; Huang, Fenglou; Liang, Yan; Yang, Zaixing; Zhong, Renqian
Abstract Background and Aim MicroRNA, as an important regulator of gene expression, has been found to be associated with several diseases. MicroRNA expression profiles have been identified in several autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis. However, the expression profile in peripheral blood mononuclear cells (PBMCs) from primary biliary cirrhosis (PBC) patients and the role of microRNA in PBC remained unclear. The present study aimed to explore abnormal microRNA regulation in PBC. Methods MicroRNA array was performed in PBMCs obtained from PBC patients versus healthy controls. Then, six of the 17 differentially expressed microRNAs were confirmed using quantitative real‐time polymerase chain reaction. Based on bioinformatics analysis, we identified the potential biological processes and significant signaling pathways affected by these microRNAs, and generated the microRNA–gene network. Results According to microRNA array, a total of 17 microRNAs were found to be differentially expressed. Six microRNAs have been validated using quantitative real‐time polymerase chain reaction, and the results were consistent with microRNA array analysis. The bioinformatics analysis showed that the potential target genes of these microRNAs were involved in cell proliferation, cell differentiation, apoptosis, and signal transduction. Similarly, these microRNAs also affected endocytosis, mitogen‐activated protein kinase signaling pathway, transforming growth factor‐β signaling pathway, Wnt signaling pathway, calcium signaling pathway, etc. Conclusion In the present study, 17 microRNAs were identified to be differentially expressed in PBMCs from PBC patients. Functional bioinformatics analysis demonstrated that prediction genes targeted by these microRNAs were involved in multiple biological processes and signaling pathways. The present study offers intriguing new perspectives on the involvement of microRNA in PBC, but the precise mechanisms need to be validated further.